Ed Gamber, Gordon Carruthers, Jim Kosloff and Jim Carruthers - (Author); (Interviewer); (Publisher) (1930)
Photograph - Four men at Pelican Portage, Alberta. A note on the back reads: #4 and #2: the trader and his brother. #4 drowned in 1935, never found. Left to right: Ed Gamber, Gordon Carruthers, Jim Kosloff and Jim Carruthers